Efficacy of lone-pair electrons to engender ultralow thermal conductivity. (15th January 2016) - Du, Baoli; Chen, Kan; Yan, Haixue; Reece, Michael J.
Graphical abstract: Abstract: IB –VA –VIA compounds with intrinsically low lattice thermal conductivity have attracted considerable attention because of their potential for thermoelectric application. The anharmonicity in the lattice vibrations produced by the lone-pair electrons of nominally trivalent group VA elements may significantly reduce their thermal conductivity to a very low value (<1 W m −1  K −1 ). We designed two types of material systems, AgLa x Sb1− x Te2 ( x  = 0, 0.01, 0.03, and 0.05) and Cu12 Sb4 S16− x ( x  = 0, 1, 2, and 3) composites, to investigate the effect of electronic bonding at the Sb site on thermal conductivity. In both cases the experimental results support our hypothesis that the anharmonicity introduced by lone pair electrons significantly reduces thermal conductivity.